Indigenous Data Matters: Finding Data for First Nations, Inuk and Metis Peoples in Canada ... - Cooper, Alexandra; Manuel, Kevin (Zenodo, 2023)
Based on the work by three academic data professionals who created the Data on Racialized Populations in Canada guide, the presenters will go into more detail about finding data for First Nations, Inuk and Metis Peoples in Canada. The presentation will explore the historical nature of some Indigenous data sources with examples that will be provided of how the federal government of Canada has collected data on Indigenous peoples, often through a colonial lens. There will be a focus on how terminology necessary for searching may include language that can be problematic and/or offensive to contemporary users. Accordingly, the content will illustrate how the vocabulary used to refer to racial, ethnic, religious and cultural groups is specific to the time period when the data was collected and does not reflect the attitudes and viewpoints of contemporary society. More recent trends of inclusive terminology will also be explored and how this reaffirms Indigenous identity in the data. Finally, an overview of data ...